Deep eutectic solvents-halophilic cellulase system: An efficient route for in situ saccharification of lignocellulose - Nagoor Gunny, Ahmad Anas; Arbain, Dachyar; Javed, Muhammad; Baghaei-Yazdi, Namdar; Gopinath, Subash C.B.; Jamal, Parveen (Elsevier, 2019)
Pre-treatment of lignocellulosic biomass is essential for the cost-effective saccharification process to produce fermentable sugars. In this study, Deep Eutectic Solvents (DESs) and halophilic cellulase system were used as a new green and cost-effective approach for lignocellulose hydrolysis. The stability and compatibility between DES and halophilic cellulase for lignocellulose hydrolysis were investigated by monitoring the stability of halophilic cellulase in the occurrence of different concentrations of DESs. It was found that halophilic cellulase showed higher stability in the occurrence of 10–20% (v/v) DES. It has been noticed that 20% of DESs, enhanced 2–3 folds in the release of glucose. The compatibility of the DES-halophilic cellulase system has been further evaluated and improved the saccharification efficiency even at high solid loadings. Using the system , saccharification of the rice husk produced three folds of glucose higher than the untreated sample. The yield was estimated to be higher than 1 mM of glucose using the halophilic cellulase -DES system with the hydrolysis for 36 h. DESs-halophilic cellulase system offers a good alternative compared to the available lignocelluloses pre-treatment method in terms of cost, environmental and